t+3-1t=3(2t-3)

Simple and best practice solution for t+3-1t=3(2t-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for t+3-1t=3(2t-3) equation:



t+3-1t=3(2t-3)
We move all terms to the left:
t+3-1t-(3(2t-3))=0
We add all the numbers together, and all the variables
-(3(2t-3))+3=0
We calculate terms in parentheses: -(3(2t-3)), so:
3(2t-3)
We multiply parentheses
6t-9
Back to the equation:
-(6t-9)
We get rid of parentheses
-6t+9+3=0
We add all the numbers together, and all the variables
-6t+12=0
We move all terms containing t to the left, all other terms to the right
-6t=-12
t=-12/-6
t=+2

See similar equations:

| b/10=-4 | | 5i-6=9 | | 13x-33=180 | | -3(1+5n)-1=-94 | | (0.5)^(1/t)=0.9 | | f(0)=4(0)^3-2(0)^2+0+3 | | 3x×9=81 | | 28-(3c+4=(c+3)+c | | 5x+6+8x-39=190 | | -8v+9=-7v | | 8-9y=-8y | | x−1=(2−x)2 | | 1-x+5=11 | | 5x+4(3x-8)=13x+4 | | n-5/6=-4 | | -4x+1=-22 | | 0.5=0.9^t | | c+(3²-3)=21 | | -4(-1+6n)+3=-161 | | 5t−6=6t | | .06n-17=-65 | | 4x-3.3=5x+12.2 | | -2+14x=5x+34 | | m1+63=180 | | f−26=44 | | -5+3x=-48-40x | | t+37=79 | | 8k-3=6k+17* | | –24+12d=2(d–3)+22d | | 4.5-7.2x=3.4x-4.95 | | 10x+7=11x | | 36−1÷26(4x)=27-1÷26(3x) |

Equations solver categories